High-resolution climate change projections and their adaptation planning implications for small basins in Egypt, Jordan, Lebanon and the Occupied Palestinian Territories - Bergaoui, Karim; Belhaj Fraj, Makram; Abeyrathna, Wasudha Prabodhani; Fragaszy, Stephen; Samarasekara, Vidhisha (International Water Management Institute, 2024)
This report collates and synthesizes the findings from comprehensive climate baseline assessments and bias-corrected and statistically downscaled climate projections for four distinct areas: Ras Baalbeck in Lebanon, Abu Al-Matamir in Egypt, Wadi Al-Seer in Jordan, and Wadi Al-Faria’a in the West Bank of the Occupied Palestinian Territories (OPT).